2016
DOI: 10.1144/sp429.2
|View full text |Cite
|
Sign up to set email alerts
|

Depositional characteristics of the northern South China Sea in response to the evolution of the Pearl River

Abstract: Geochemical data from South China Sea sedimentary rocks show the effects of both source composition and depositional environments. This enables us to link tectonic trends with erosion in the Pearl River region since c. 32 Ma. In particular, a shift in the geochemistry appears to signal a response to a well-recorded regional tectonic event at c. 23-25 Ma, probably corresponding to a jump in the seafloor spreading axis from the west to the SW within the South China Sea. This may correlate with the uplift of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 25 publications
(33 reference statements)
2
55
0
Order By: Relevance
“…3; Tu et al, 1991;Ho et al, 2000). 2) The Miocene sediments from the PRMB have the relatively high CaO content and low Al 2 O 3 content, which may indicate a provenance from the Paleozoic carbonate rocks in South China (Shao et al, 2013). Northern Hainan Island and South China thus seem less likely as the source areas for the Shenhu Uplift.…”
Section: Provenance Modification Inside the Basinsmentioning
confidence: 99%
“…3; Tu et al, 1991;Ho et al, 2000). 2) The Miocene sediments from the PRMB have the relatively high CaO content and low Al 2 O 3 content, which may indicate a provenance from the Paleozoic carbonate rocks in South China (Shao et al, 2013). Northern Hainan Island and South China thus seem less likely as the source areas for the Shenhu Uplift.…”
Section: Provenance Modification Inside the Basinsmentioning
confidence: 99%
“…[] favored a sediment source from the southward drifting Palawan Continental Terrane, but their interpretation of geochemical signatures in terms of potential source areas were largely derived from modern sediments, which may not fully represent those of the Paleogene source‐to‐sink systems. In contrast to these interpretations of a southern margin source for the basin sediments, most provenance studies emphasize a northern provenance from South China based on sedimentary and conventional geochemical evidence [e.g., Clift et al ., ; Shao et al ., ; Lan et al ., ]. This viewpoint is also supported by apatite fission track analyses from southeastern South China that revealed rapid cooling episodes during the Eocene‐Oligocene [ Yi et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…The studies cover the major rivers that cross the mainland of China, like the Red River (Clift et al, ), the Pearl River (Shao et al, ), and the Yangtze River (Zhang et al, ; Zheng et al, ), and while they emphasize drainage expansions and reorganizations, on the northern margin of the SCS, as a primary influence on onshore and offshore sediment, the timing documented by these studies do not match the syn‐rift sequences analyzed in this paper. For the Pearl River system, several important changes in geochemical composition have been recorded in sediments from boreholes in the PRMB and ODP Site 1,148 (Shao et al, ). Among the events, the most pronounced occurred at ∼23.8 Ma and is interpreted to have been caused by the catchment expansion to western plateau of Pearl River (Shao et al, ).…”
Section: Discussionmentioning
confidence: 82%
“…Indosinian gneissic granites formed in the early Triassic, with the zircon U‐Pb ages of 250–242 Ma, while massive granites range from 248 to 202 Ma (Wang et al, ). Because sediment in the Zhu 1 depression was dominately dip‐fed (Jiang et al, ; Liu et al, ; Shao et al, ; Shu et al, ), grains with Paleozoic and Triassic ages, shown in Figure , are likely to have been sourced from the rocks in the SCB. The number of zircons that fall into this Kwangsian interval varies substantially from the Wenchang (6 of 137, 4%; 1 of 83 in lower Wenchang to 5 of 54 in upper Wenchang Formation) to the Enping (44 of 178, 24%) to the Zhuhai Formation (34 of 94, 36%) (Figures and ) and confirms that sediment contributed from regional sources increased through time.…”
Section: Discussionmentioning
confidence: 99%